Recent trends in exposure to secondhand smoke in the United States population - Mastey Vera; Baker Christine L; Burton Tanya; Chen Chieh-I; Mannino David (BMC, 2010)
Abstract Background Previous research using the National Health and Nutrition Examination Surveys (NHANES) data documented a significant downward trend in secondhand smoke (SHS) exposure between 1988 and 2002. The objective of this study was to assess whether the downward trend in exposure continued from 2001 through 2006. Methods We analyzed data from the 2001-2006 NHANES to estimate exposure of nonsmokers to SHS. Geometric means of serum cotinine levels for all nonsmokers were computed. Results Overall serum cotinine levels (95% Confidence Intervals) in 2001-2002, 2003-2004, and 2005-2006 were 0.06 ng/mL (0.05-0.07), 0.07 ng/mL (0.06-0.09), and 0.05 ng/mL (0.05-0.06), respectively. Subgroup analysis by age, gender, and race/ethnicity groups showed similar trends in cotinine levels. Children, males, and non-Hispanic Blacks had higher cotinine levels than adults, females, and non-Hispanic Whites and Mexican Americans, respectively. Insignificant P values from the Wald test indicate that serum cotinine levels did not differ over time. Conclusions The long-term trend of declining exposure to SHS among nonsmokers appears to have leveled off. However, disparities noted in previous research persist today, with the young, non-Hispanic Blacks, and males experiencing higher levels of exposure.